A review of sensory quality control and quality assurance for alcoholic beverages - McGrew, Don (Kansas State University, 2011)
Tools are available, through various reference books, to develop a purposeful sensory quality program. Some companies already have a strong sensory program in place; others may require a cultural change to facilitate the implementation. This paper indicates some of the challenges to be overcome, covers some current quality control (QC) sensory practices and addresses advantages and disadvantages of expert tasters Some specific issues regarding sensory evaluations of alcohol beverages are discussed and critical factors in production are reviewed with discussion on the potential for off taint development.
Keywords: Alcohol beverages; Sensory quality; Expert tasters; Off odors; Quality control; Food Science (0359)